Statistical Analysis to Evaluate The Service Quality at Community Health Center in Padang, Indonesia - Aidinil Zetra; Ferra Yanuar (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Healthcare provider have to take care of patient satisfaction. Therefore, the management should do a kind of evaluation to examine the patient satisfaction on the corresponding services. The purpose of this study is to evaluate the service quality of public health centre and to identify the attributes of services to be improved. This study was cross sectional study conducted by distributing the questionairres to the patients of public health centre in Padang, Indonesia from April to June 2015. This study involved 446 respondents with complete information. Customer Satisfaction Index (CSI) was used to measure the service quality of corresponding public health centre. Importance Performance Analysis (IPA) approach was also applied to identify any attributes to be improved. The respondents of this study were very satisfied with the health service that they ever got. All attributes of service were plotted in four quadrants. This study proved that CSI and IPA methods are pertinent to be applied to measure patient satisfaction and identify any attributes of service to be maintained or improved.